2016
DOI: 10.1080/13607863.2016.1232367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a social intervention of choice vs. control on depressive symptoms, melancholy, feeling of loneliness, and perceived togetherness in older Finnish people: a randomized controlled trial

Abstract: The intervention did not alleviate depressed mood. Positive changes over time were observed in loneliness, feelings of melancholy, attachment, and guidance but these occurred independently of the intervention. Our secondary analysis suggests that the intervention increased perceived social integration. In sum, the effects of the intervention were moderate only and did not expedite further overcoming depressive mood or loneliness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 34 publications
1
30
0
1
Order By: Relevance
“…After applying predefined inclusion and exclusion criteria, we included 16 studies 34-49 -9 from systematic reviews 34-37, 39, 41, 42, 45, 46 and 7 from primary study searches. 38,40,43,44,[47][48][49] Of the 16 included studies (7 randomized controlled trials [RCTs], 38, 44-49 8 pre-post, [34][35][36][37][39][40][41][42] and 1 cross sectional with a post-test survey 43 ) including 17,656 patients, 5 involved physical activity interventions, [45][46][47][48][49] 5 involved social interventions, 35, 40-42, 44 4 involved arts and recreation-based interventions, 34,[36][37][38] and 2 involved improving health services access. 39, Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After applying predefined inclusion and exclusion criteria, we included 16 studies 34-49 -9 from systematic reviews 34-37, 39, 41, 42, 45, 46 and 7 from primary study searches. 38,40,43,44,[47][48][49] Of the 16 included studies (7 randomized controlled trials [RCTs], 38, 44-49 8 pre-post, [34][35][36][37][39][40][41][42] and 1 cross sectional with a post-test survey 43 ) including 17,656 patients, 5 involved physical activity interventions, [45][46][47][48][49] 5 involved social interventions, 35, 40-42, 44 4 involved arts and recreation-based interventions, 34,[36][37][38] and 2 involved improving health services access. 39, Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 16 studies aimed at reducing social isolation or a related construct, 34-49 4 40, 44, 45, 48 (3 RCT, 1 pre-post) demonstrated measurable improvement in loneliness, social capital, or social participation; 6 34,36,38,42,46,47 (3 RCTs and 3 pre-post) had no significant effect on loneliness, social support, or social networks; and 6 35,37,39,41,43,49 (1 RCT, 4 pre-post, and 1 cross-sectional) did not report an effect or the effect could not be determined. Five (2 RCTs 46, 48 and 3 pre-post 36, 39, 42 ) of 16 studies reported improvements in health outcomes, including quality of life, frailty, depression, diet, functionality, stress, and chronic pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for the present exploratory analyses the social intervention group comprised 104 and the self-directed group 118 participants. The sampling procedure and study design have been described in more detail elsewhere (Pynnonen et al, 2016).…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…This article reports an exploratory observational analysis of data collected as part of a randomized controlled trial that targeted community-dwelling older people who reported negative mood or loneliness at study entry (GoodMood; ISRCTN78426775) (Pynnonen, Tormakangas, Rantanen, Tiikkainen, & Kallinen, 2016). The objective of the study was to investigate longitudinal associations of the six dimensions of perceived togetherness with depressive symptoms and feelings of loneliness.…”
Section: Introductionmentioning
confidence: 99%